Differentiation of self, emotion management skills, and nomophobia among smartphone users: The mediating and moderating roles of intolerance of uncertainty - Ercengiz, Mustafa; Yildiz, Banu; Savci, Mustafa; Griffiths, Mark D. (Routledge Journals, Taylor & Francis Ltd, 2024)
The use of smartphones has become increasingly widespread, especially among university students. There is a growing body of research interest related to problematic and excessive use of smartphones. Problematic smartphone usage can cause negative emotions such as intense anxiety and distress when the smartphone cannot be used (e.g., nomophobia), and can lead to negative consequences on mental health. In the present study, two different mediating and moderating effects in which nomophobia was the outcome variable were examined. Firstly, the mediating effect of intolerance of uncertainty was tested in the relationship between differentiation of self and nomophobia. Secondly, the mediating effect of intolerance of uncertainty was tested in the relationship between emotion management skills and nomophobia. Third, the moderating effect of intolerance of uncertainty was tested in the relationship between differentiation of self and nomophobia. Finally, the moderating effect of intolerance of uncertainty was tested in the relationship between emotion management skills and nomophobia. The present study comprised 398 university students (250 females and 148 males). The measures used included the Differentiation of Self Inventory-Revised, Emotions Management Skills Scale, Nomophobia Questionnaire, and Intolerance of Uncertainty Scale. Findings demonstrated that the mediating of intolerance of uncertainty were statistically significant in the relationships examined, but the moderating effects of intolerance of uncertainty were not. Research results are discussed in the light of the related literature and suggestions are presented for future researchers.
Keywords: Smartphones; differentiation of self; emotion management skills; intolerance of uncertainty; nomophobia